Disordered eating practices in gastrointestinal disorders. (1st January 2015) - Satherley, R.; Howard, R.; Higgs, S.
Highlights: Evidence of disordered eating patterns in GI disease was reviewed. The prevalence of disordered eating in gastrointestinal disease was 5.3–44.4%. This was associated with distress, symptom severity and dietary management. A conceptual model of disordered eating in GI disease was developed. Abstract: Purpose: To systematically review evidence concerning disordered eating practices in dietary-controlled gastrointestinal conditions. Three key questions were examined: a) are disordered eating practices a feature of GI disorders?; b) what abnormal eating practices are present in those with GI disorders?; and c) what factors are associated with the presence of disordered eating in those with GI disorders? By exploring these questions, we aim to develop a conceptual model of disordered eating development in GI disease. Methods: Five key databases, Web of Science with Conference Proceedings (1900–2014) and MEDLINE (1950–2014), PubMed, PsycINFO (1967–2014) and Google Scholar, were searched for papers relating to disordered eating practices in those with GI disorders. All papers were quality assessed before being included in the review. Results: Nine papers were included in the review. The majority of papers reported that the prevalence of disordered eating behaviours is greater in populations with GI disorders than in populations of healthy controls. Disordered eating patterns in dietary-controlled GI disorders may be associated with both anxiety and GI symptoms. Evidence concerning the correlates of disordered eating was limited. Conclusions: The presence of disordered eating behaviours is greater in populations with GI disorders than in populations of healthy controls, but the direction of the relationship is not clear. Implications for further research are discussed.